The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/s19020348
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Analyzing the Impact of Intra-System and Inter-System Interference on DME Based on Queueing Theory

Abstract: In order to use Distance Measuring Equipment (DME) properly, the impact of intra-system and inter-system electromagnetic interference must be analyzed firstly. However, the error of interference analysis using present methods based on pulse overlap is large when there are more aircraft. The aim of this article is to study a method of analyzing interference on DME whether the number of aircraft is small or not. According to the flow chart of DME signal, we studied the limitations of present methods; then constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It ranges from the analysis of service chains to arbitrary complex queues of huge network systems. It is usually used to analyze the probability distribution in a continuous-state space [44,45]. Several models of queuing systems are represented by Kendall's notation to classify system types and their queuing events.…”
Section: Queuing Theorymentioning
confidence: 99%
“…It ranges from the analysis of service chains to arbitrary complex queues of huge network systems. It is usually used to analyze the probability distribution in a continuous-state space [44,45]. Several models of queuing systems are represented by Kendall's notation to classify system types and their queuing events.…”
Section: Queuing Theorymentioning
confidence: 99%
“…where S(X, t) is an additive mixture of the signal DME S 1 (X, t) (8), and the narrowband interference u(t) (3)- (7). The input signal models ( 8), (14), and (15) were used to derive algorithms for DME signal processing under narrowband interference conditions. A procedure similar to that described in [1] has been used in cases wherein the algorithms for DME signal processing under broadband fluctuation interference conditions are given.…”
Section: Dme Signal Processing Under Narrowband Interference Conditionsmentioning
confidence: 99%
“…An analysis of intra-system and inter-system electromagnetic interference in the DME system is given in [14]. It is reported that large errors may be made in interference analysis if a large number of aircraft cooperate with the DME ground equipment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation